Injections Site Reactions and Biologics for Psoriasis: A Questionnaire Based Real Life Study - Matteo M; Battista T; Noto M; Picone V; Fabbrocini G; Ruggiero A; Genco L (Dove Medical Press, 2023)
Megna Matteo, Teresa Battista,* Matteo Noto,* Vincenzo Picone, Gabriella Fabbrocini, Angelo Ruggiero,* Lucia Genco* Department of Clinical Medicine and Surgery - Section of Dermatology, University of Naples Federico II, Naples, Italy*These authors contributed equally to this workCorrespondence: Angelo Ruggiero, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email angeloruggiero1993@libero.itBackground: Biologic selection for psoriasis treatment should take into account numerous factors including injection site reactions (ISRs) such as swelling at the injection site, pain, burning, erythema, all possibly reducing patient adherence.Methods: A 6-months observational real life study was performed involving psoriasis patients. Inclusion criteria were age ≥ 18 years, moderate-to-severe psoriasis diagnosis since at least 1 year, patients being on biologic treatment for psoriasis ≥ 6 months. A 14-item questionnaire was administered to all patients enrolled to assess whether the patient ever experienced ISRs after the injection of the biologic drug.Results: 234 patients were included: 32.5% received an anti-TNF-alpha drug, 9.4% received anti-IL12/23, 32.5% received an anti-IL17, 25.6% received an anti-IL23. 51.2% of study population reported at least one symptom related to ISR. 35.9% of patients experienced pain, 31.6% swelling, 28.2% burning sensation and 17.9% erythema. 3.4% of the surveyed population experienced anxiety or fear of the biologic injection due to ISRs symptoms. The greater incidence of pain was registered in anti-TNF-alpha and anti-IL17 groups (47.4% and 42.1%, p< 0.01). Ixekizumab proved to be the drug with the highest rate of patients experiencing pain (72.2%), burning (77.7%) and swelling (83.3%). No patients reported biologics discontinuation or delay for ISRs symptoms.Conclusion: Our study highlighted that each different class of biologics for psoriasis was linked to ISRs. These events are more frequently reported with anti-TNF-alpha and anti-IL17.Keywords: psoriasis, injection site reactions, biologic therapy